2016
DOI: 10.1080/09669760.2015.1133073
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts and resistance: potentials for democracy learning in preschool

Abstract: The study aims to develop knowledge about learning for democracy in ECEC, through investigating acts of resistance in conflicts and examine these as potentials for democracy learning. The study is informed by Mouffe's theoretical ideas about conflicts as a prerequisite for democracy. The research questions are: What kind of conflicts can be identified in everyday interactions in preschool? How do children and teachers express and maintain resistance in conflicts? What potentials for democracy learning are ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 8 publications
0
25
0
2
Order By: Relevance
“…Moving children beyond multiplist perspectives means that rather than simply accepting all opinions as equal, the children would be supported to engage in critical reflection (Sigauke, ). Winton () suggested that engaging with and evaluating conflicting points of view helps children to develop their ideas about equity and justice (Bjervås, ; Johansson & Emilson, ; Pálmadóttir, ). This may be promoted through dialogically organized classrooms (DOCs; Lunn Brownlee et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moving children beyond multiplist perspectives means that rather than simply accepting all opinions as equal, the children would be supported to engage in critical reflection (Sigauke, ). Winton () suggested that engaging with and evaluating conflicting points of view helps children to develop their ideas about equity and justice (Bjervås, ; Johansson & Emilson, ; Pálmadóttir, ). This may be promoted through dialogically organized classrooms (DOCs; Lunn Brownlee et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…While children shift from absolutist, black, and white perspectives to more multiplist thinking, teachers can play a role in stimulating children to think critically by providing experiences that include analysing conflicting points of view in terms of value judgements (Johansson & Emilson, ; Lunn Brownlee et al ., ; Winton, ). Understandings about social justice and inequality can be developed when children are assisted to engage in critical thinking in relation to norms, oppressions, and injustices (Bjervås, ; Thornberg, , ; Zachrisen, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has highlighted challenges that might arise in conflict situations, which means that people have different perspectives, values or aims for their thoughts and actions (Doppler-Bourassa et al, 2008). Different types of resistance can occur in such events (Johansson & Emilson, 2016;Markström & Halldén, 2009;Skoglund, 2019). In the Scandinavian countries conflicts and resistance are considered important for democratic learning, where expressions of different interests, perspectives and resistance are important events in everyday life in kindergartens.…”
mentioning
confidence: 99%
“…In the Scandinavian countries conflicts and resistance are considered important for democratic learning, where expressions of different interests, perspectives and resistance are important events in everyday life in kindergartens. Children are expected to handle conflicts verbally, and through negotiations and compromises, while teachers are expected to support these negotiations in a democratic and rational way (Grindheim, 2013;Johansson & Emilson, 2016;Skoglund, 2019).…”
mentioning
confidence: 99%